Synchrony and Diachrony of the Postgraduate Program in Special Education at the Faculty of Higher Studies Zaragoza (FESZ): Balance and Perspectives - Acle Tomasini, Guadalupe (2022)
Introduction: To design a postgraduate study plan is an relevant task for what is expected in the future about the training of its students. To implement it and to adapt it to the different demands that are manifested over time are major words. Objective: is to describe the synchronic and diachronic elements underlying the postgraduate program in Special Education at the FESZ since 1987 to date. It shows the evolution of the postgraduate course over time, the theoretical bases that support it, the situation teachers and students regarding graduation, no graduation and occupational level. Discussion: The dynamism from its implementation is recognized, the relationship that it has kept with various factors in which it has been immersed, both the administrative and academic of the institution as well as other external ones: political, economic, and scientific. It concludes with the contributions made to the field of special education and the areas of opportunity, both disciplinary and formative, in face of future changes.